2023
DOI: 10.3847/2041-8213/acd778
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Evolution of Switchbacks in the Inner Heliosphere: Parker Solar Probe Observations

Abstract: Since its launch in 2018, the Parker Solar Probe (PSP) mission revealed the presence of numerous fascinating phenomena occurring closer to the Sun, such as the presence of ubiquitous switchbacks (SBs). The SBs are large magnetic field deflections of the local magnetic field relative to a background field. We investigated the statistical properties of the SBs during the first 10 encounters between 13.28 and 58 solar radii (R ⊙) using data from the SWEAP and FIELDS suites on board PSP. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…Interestingly, as we have found to be the case with SMFRs, SB occurrence is correlated with bulk velocity (Mozer et al 2021;Jagarlamudi et al 2023). We have shown that the occurrence of SMFRs is correlated with the average bulk velocity as a consequence of a nearly constant radial density (combined with a slightly higher radial density in faster solar wind types).…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, as we have found to be the case with SMFRs, SB occurrence is correlated with bulk velocity (Mozer et al 2021;Jagarlamudi et al 2023). We have shown that the occurrence of SMFRs is correlated with the average bulk velocity as a consequence of a nearly constant radial density (combined with a slightly higher radial density in faster solar wind types).…”
Section: Discussionsupporting
confidence: 67%
“…At present, it is unclear to us specifically how our successive SMFR observations relate to the findings in all these previous reports on the relation between flux ropes and switchbacks. Nevertheless, we note that one difference lies in the timescale of the flux ropes, which is ∼0.5 hr or longer in our SMFRs, which is much longer than those for flux ropes and switchbacks considered in previous works (Drake et al 2021;Agapitov et al 2022) although the recent work by Jagarlamudi et al (2023) included long-duration switchbacks measured by the PSP. Further in-depth work on how our SMFR observations link to all these issues is desired.…”
Section: Conclusion and Discussionmentioning
confidence: 63%
“…At PSP, upstream of the shock, the magnetic field is mostly radial and interspersed with one-sided Alfvénic fluctuations (Gosling et al 2009) of the magnetic field and ion bulk velocity, known as magnetic switchbacks, with moderate-amplitude angular deflections in the magnetic field, as expected for very low heliocentric distances (e.g., Jagarlamudi et al 2023). SBs are a crucial feature of the solar wind in the inner heliosphere, as extensively shown in previous literature (Dudok de Wit et al 2020;Krasnoselskikh et al 2020;Larosa et al 2021;Liang et al 2021;Pecora et al 2022;Jagarlamudi et al 2023;Liu et al 2023;Raouafi et al 2023). Here, we have the opportunity to study how such structures are processed by shock waves, a crucial point of this work summarized in Section 3.2.…”
Section: Event Overviewmentioning
confidence: 78%